PEMANFAATAN LIMBAH BAMBU SEBAGAI MEDIA KREASI GUNA MENGEMBANGKAN KREATIVITAS ANAK PANTI ASUHAN KRISTEN TANGMENTOE MELALUI METODE R-TIGA - Biringkanae, Astriwati; Alik, Jaya; Fransisca Imlekiana, Adelia; Putri, Olivia Anjeli; Sapu, Arianto; Datu, Yuliana (Yayasan Education and Social Center, 2024)
The problem of lack of creativity of the children of the Tangmentoe Christian orphanage needs to be improved. One of the activities that can be done to increase children's creativity is by processing bamboo waste into goods with selling value. Bamboo waste itself is one of the problems in partner areas. Untreated bamboo waste often becomes a nest of diseases and a place for mosquitoes to live. The purpose of this program is to increase the knowledge, skills, and creativity of the children of the Tangmentoe Christian Orphanage. The method of implementing this activity consists of preparation, implementation (training and mentoring), and evaluation. The results of the program are 100% achieved outputs in the form of partner manuals, progress reports, final reports and social media accounts. Another result obtained is the existence of income and profits to help meet the daily needs of children in orphanages. It can be concluded that through the program of utilizing bamboo waste as a creative medium, it can increase the knowledge, skills and creativity of the children of the Tangmentoe Christian Orphanage.